Metas de Inflación y Efectividad de la Politica Monetaria en el Perú - Roca Garay, Richard (2013)
This paper reviews the performance of monetary policy to control inflation in Peru compared to the rest of the world and finds that inflation in Peru was at a medium level. Not too high, not too low compared to the inflation level of other countries that apply the inflation targeting framework.